Flood risk assessment and flow modeling of the Stalos stream area. Issue 3 (7th April 2022) - Goumas, Christos; Trichakis, Ioannis; Vozinaki, Anthi-Irini; Karatzas, George P.
Abstract: The objective of the work performed in this paper was to implement flood risk assessment on the Stalos stream area, west of the city of Chania, Crete, Greece, utilizing two separate methods complementing each other. The first stage was a GIS-based approach, utilizing the ArcGIS software, by determining the crucial factors affecting flood risk, and subsequently scoring and combining the factors into a final raster, with each factor appropriately scored. The second stage involved the flow modeling of a stream located in the study area of Stalos, upon which a meteorological station was installed upstream, in addition to a radar flow meter downstream, at the stream's output to the sea. For the purposes of modeling, the MIKE HYDRO River software pack was utilized, in addition to the ArcGIS software for digitizing cross sections and editing the Digital Elevation Model of the area. From this methodology, the flood risk of the area was determined, and additionally, the low overflow risk of the stream was determined, as there was no point across the stream, where the water level in the stream reached dangerous levels, despite sustained heavy precipitation. HIGHLIGHTS: Flood risk assessment with use of GIS tools and visualization of risk and risk parameters. Ease of use. Widespread application and use of GIS tools and easily obtainable open data.